Mechanical Processing of Sintered Materials : Finite Element Analysis Of Sinter-Forging Processes - Singh, Saranjit; Chandrasekhar, Polymersetty (Sciendo, 2020)
Mechanical processing of sintered materials in the form of metal powder preforms includes techniques such as sinter-forging, sinter-extrusion, sinter-rolling etc. One technique, which has aroused interest globally for producing high performance components economically, is sinterforging, which combines the advantages associated with powder metallurgy and conventional forging techniques. The process is attractive because it avoids large number of operations, high scrap losses and energy consumption associated with conventional manufacturing processes. The technology, though have been extensively applied throughout the world for manufacture of numerous components, still requires to be explored from several perspectives. The objective of the present book is to study, explore and investigate the deformation characteristics during mechanical processing of the sintered materials. ABSTRACTING & INDEXING Mechanical Processing of Sintered Materials is covered by the following services: EBSCO Discovery Service Google Scholar J-Gate Naviga (Softweco) Primo Central (ExLibris) ReadCube Summon (ProQuest) TDOne (TDNet)